(untitled) (European Journal of Marketing and Economics, 2022)
Under the current conditions of the economic development, the management of entities requires information in order to make efficient economic decisions to achive the objectives by taking the respective risks as well. To achieve this goal, among other things, the organization of effective internal control systems and accounting is important. Financial scandals at the beginning of the XXI century highlighted the deficiencies and indicated the need to establish effective internal control systems and risk management. Small and medium enterprises currently represent the major part of economic activities throughout the world. In Albania, they represent the largest proportion of all types of enterprises, providing a lot of opportunities for employment. Mechanisms of internal control are a tool and a way of monitoring the human resources activities of SMEs. It plays an important role in the prevention and detection of fraud and protection of physical and intangible resources, and leading to high efficiency and smooth functioning of the business. This study examines and describes the effectiveness of internal control systems in Albanian small and medium size enterprises. The study focuses on the five main components of internal control and their impact on achieving the companys objectives. To achieve these objectives we formulate one research question: To what extent does the internal control system of SMEs comply with the principles of effective internal control? The literature review chapter is based from various resources such as books, articles and online papers. We will use questionnaire to collect data pertaining to the five essential and interrelated components of internal control: control environment, risk assessment, information and communication, monitoring and control activities. After obtaining adequate theoretical framework and practical data, a comprehensive analysis is carried out based on these data. This study has shown that SMEs in Albania has a solid and effective internal control system, but still it needs more improvement and generally it requires more attention from the board members.